A Scientometric Analysis of Debt and Risk in Islamic Bonds - Maman Faudzi; Tiara Salsabila; Muhammad Arsy Ramdhan Gozali Putra; Agus Salim; Firsty Ramadhona Amalia Lubis; Rifki Khoirudin; Lestari Sukarniati (Universitas Darussalam Gontor, 2023)
Debt and risk have become one of the most emerging debates on Islamic bond studies in the last decade. Some of the topics and research areas have been expanded to provide a huger of analysis in Islamic bonds. However, the majority of earlier studies did not use bibliometric analysis to provide a predetermined framework for the study of Islamic bonds. Thus, this study attempts to analyze emerging topics and trends in Islamic bonds and explore research directions. We employ bibliometrics to analyze 377 articles published on journals indexed by Web of Science (WOS) and Scopus databases from 1984 to 2022. The results reveal that, research in Islamic bonds is growing during the period of analysis. The thematic evolution shows that debt and risk were the most trending topics before and after 2018 of the cutting periods, respectively.